A sociological interpretation of emerging properties in STI transmission dynamics: walk-betweenness of sexual networks. (22nd November 2010) - Youm, Yoosik
Abstract : Objectives: This study is intended to examine the role of bridges in sexually transmitted infection (STI) transmission dynamics as an emerging property that is an unintended and aggregate result of individual behaviours or preferences. It also provides an empirical illustration using a newly customised measure of bridging activities—namely, 'walk-betweenness'. Methods: Participants in the Chicago Sexual Acquisition and Transmission of HIV Cooperative Agreement Program (SATHCAP) recruited from August 2005 through October 2006 were used in the analysis. They were recruited through respondent-driven bias-adjusted snowball sampling, beginning with six 'seed' recruiters who were given seven coded coupons to distribute to eligible peers for inclusion in the study: three coupons for drug users or men who have sex with men (MSM) regardless of drug use; three coupons for sexual partners; and one coupon for either a non-drug-using sex partner or, if the seed participant was an MSM, for a female sex partner. A walk-betweenness score was created for each of the 77 community areas in Chicago. The SATHCAP questionnaire was used to ask respondents for the neighbourhood locations in which they had had sex in the previous 6 months. The total number of respondents was 1068. Results: The results of the study confirm the existence of hidden bridging communities in the Chicago area. Although these communities were essential to AIDS transmission, they might have been largely ignored because of their low prevalence rates. Conclusions: The role of bridging positions in STI transmission dynamics can be considered as an emerging property that is an aggregate result from individual sexual behaviours or preferences. A newly customised measure of bridging positions is needed to identify this property adequately.